Neutralización del efecto hemorrágico inducido por veneno de Bothrops asper (Serpentes: Viperidae) por extractos de plantas tropicales - Castro, Oscar (Universidad de Costa Rica, 1999)
Organic extracts representing 48 species included in 30 families of Costa Rican tropicalp1ants were evaluated fortheir abiJity to neutralize hemorrhagic acfívity lnduc.ed by the venom of the snake Bothrops aspero Abioassay in míce was used, based ortintráderrnal injection of either venom orvenom-extract mixtíin:l.s followed py the rneasurement ofhemorrhagic areas: Total inhibition of henmrrhage wasobsetved with the ethanolic;ethyl and .aqueous extracts¡ofBur;w{¡ simaruba, Clusia torresii, C. pafmana, Croton·4ram, Persea qmericanq, Phoebebrenesü,Pimentadioica, . . Sapindussaponaria¡ Smifax cuculmeco and Virola koschnyi; C:hemicalanalysis of these extracts identified catequines,flavones, anthocyanines